Local communities perceptions of bamboo deforestation in Benishangul Gumuz region, Ethiopia - Bessie, S.; Beyene, F.; Kotu, Bekele Hundie; Goshu, G.; Mengesha, Y. (2014)
Households’ perception toward deforestation and knowledge on conservation is important for designing suitable management policies. However, more often than not local communities’ perceptions do not receive as much attention as they deserve. The study investigated local communities’ perception towards the impact of bamboo deforestation and identifies perceived impacts of bamboo deforestation. Data was obtained from a random sample of 384 households. Exploratory factor analysis and seemingly unrelated regression models were used to estimate various relationships. The result shows that 64.06 percent of respondents perceive bamboo forest cover as rapidly declining state. The factor analysis result has identified 3-latent factors (economic, environmental and social perceived impacts). The most perceived impact is economic impact with overall mean score of 3.05.Regression results showed shows that economic, environmental, and social impacts of bamboo deforestation were positivity interdependent, and influenced by some common underlying explanatory variables. These factors included: age of the household head, experience in shifting cultivation, knowledge on the resource condition, and trust among community, membership in social groups, and distance from the forest, farm size, and dependency on bamboo collection.The result recommends the need for quick bamboo forest conservation and rehabilitation activity based on the principles of collective actions and participatory forest management system. Moreover, frequent awareness creation on wildfire protection, modern charcoal preparation, shifting agricultural production system, knowledge on the resource condition were suggested for effective and sustainable use of bamboo resources in the region.Households’ perception toward deforestation and knowledge on conservation is important for designing suitable management policies. However, more often than not local communities’ perceptions do not receive as much attention as they deserve. The study investigated local communities’ perception towards the impact of bamboo deforestation and identifies perceived impacts of bamboo deforestation. Data was obtained from a random sample of 384 households. Exploratory factor analysis and seemingly unrelated regression models were used to estimate various relationships. The result shows that 64.06 percent of respondents perceive bamboo forest cover as rapidly declining state. The factor analysis result has identified 3-latent factors (economic, environmental and social perceived impacts). The most perceived impact is economic impact with overall mean score of 3.05.Regression results showed shows that economic, environmental, and social impacts of bamboo deforestation were positivity interdependent, and influenced by some common underlying explanatory variables. These factors included: age of the household head, experience in shifting cultivation, knowledge on the resource condition, and trust among community, membership in social groups, and distance from the forest, farm size, and dependency on bamboo collection.The result recommends the need for quick bamboo forest conservation and rehabilitation activity based on the principles of collective actions and participatory forest management system. Moreover, frequent awareness creation on wildfire protection, modern charcoal preparation, shifting agricultural production system, knowledge on the resource condition were suggested for effective and sustainable use of bamboo resources in the region.Households’ perception toward deforestation and knowledge on conservation is important for designing suitable management policies. However, more often than not local communities’ perceptions do not receive as much attention as they deserve. The study investigated local communities’ perception towards the impact of bamboo deforestation and identifies perceived impacts of bamboo deforestation. Data was obtained from a random sample of 384 households. Exploratory factor analysis and seemingly unrelated regression models were used to estimate various relationships. The result shows that 64.06 percent of respondents perceive bamboo forest cover as rapidly declining state. The factor analysis result has identified 3-latent factors (economic, environmental and social perceived impacts). The most perceived impact is economic impact with overall mean score of 3.05.Regression results showed shows that economic, environmental, and social impacts of bamboo deforestation were positivity interdependent, and influenced by some common underlying explanatory variables. These factors included: age of the household head, experience in shifting cultivation, knowledge on the resource condition, and trust among community, membership in social groups, and distance from the forest, farm size, and dependency on bamboo collection.The result recommends the need for quick bamboo forest conservation and rehabilitation activity based on the principles of collective actions and participatory forest management system. Moreover, frequent awareness creation on wildfire protection, modern charcoal preparation, shifting agricultural production system, knowledge on the resource condition were suggested for effective and sustainable use of bamboo resources in the region.